2022
DOI: 10.3390/economies10070172
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Regional Industrial Growth: Does Specialization Explain It?

Abstract: Being a form of territorial division of labor, economic specialization should be considered as a strategic management priority, contributing to a competitive territorial production structure and, consequently, regional economic growth. The article is devoted, firstly, to the development of a method for assessing the level of territorial division of labor based on a new coefficient of regional economic specialization; and secondly, to the investigation of regional specialization effects on economic growth. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…indicate that under the interaction of specialization agglomeration and diversification agglomeration, the impact of industrial agglomeration on urban economic resilience depends on the type of dual industrial agglomeration, showing significant heterogeneity. Gamidullaeva et al (2022) utilized econometric methods based on the extended exogenous growth model to confirm the impact of territorial specialization factors on industrial economic growth. Fritsch and Slavtchev (2008) found that in high-tech industries, there exists an inverted U-shaped relationship between innovation and industrial agglomeration; that is, excessive specialization or diversification will lead to low efficiency of regional innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…indicate that under the interaction of specialization agglomeration and diversification agglomeration, the impact of industrial agglomeration on urban economic resilience depends on the type of dual industrial agglomeration, showing significant heterogeneity. Gamidullaeva et al (2022) utilized econometric methods based on the extended exogenous growth model to confirm the impact of territorial specialization factors on industrial economic growth. Fritsch and Slavtchev (2008) found that in high-tech industries, there exists an inverted U-shaped relationship between innovation and industrial agglomeration; that is, excessive specialization or diversification will lead to low efficiency of regional innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Сложность решения этой проблемы заключается в том, что решать ее необходимо комплексно, учитывая внутреннее состояние экономики региона [7], факторы инноваций, цифровизации, транспортной инфраструктуры [8] и внешний контекст: экономическую интеграцию, изменения в мировой торговле, демографические изменения, экологические вызовы и транспортную инфраструктуру. Некоторые авторы отмечают особую значимость решения миграционного вопроса для конкурентоспособности приграничного региона, поскольку в условиях низкой рождаемости миграционные перетоки с соседней страной могут служить важным источником пополнения трудовых ресурсов [9].…”
Section: Introductionunclassified